BCIA - PAYNE L (Tufts Archival Research Center, 2007)
Missing Attachments; Memo to Kay Thomas from Lee Payne regarding the Business Council on Indoor Air (BCIA). Discusses the possibility of developing a "second tier membership" composed of companies in industries less vulnerable, but still potentially affected by, clean indoor air issues. Requests a list of potential second tier company members.